The Relationship between Communication System, Work Motivation, and Reward Management with Human Resource Development in Madrasah - Nurhayati, Nurhayati; Liana, Dina; Bon, Abdul Talib Bin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the relationship between communication systems, work motivation, and reward management on human resource development (HRD) in madrasahs. The study used a quantitative method with a correlational survey design. Data were collected through closed-ended questionnaires that had been tested for validity and reliability. A sample of 60 teachers was selected using random sampling techniques from three representative madrasahs in the region. Data analysis was conducted using correlation statistics and multiple regression in SPSS version 29. The results showed that communication systems, work motivation, and reward management had a significant effect on HRD development in madrasahs. Partially, the communication system had a positive correlation of 0.71, the strongest work motivation was 0.85, and reward management was 0.75. All three also contributed significantly simultaneously, with an F count of 94.94, exceeding the F table value of 4.01, and a combined correlation coefficient of 0.877. The regression equation revealed that work motivation and reward management had a positive impact, while the communication system also played a role, albeit with a small coefficient. These findings provide a strong basis for madrasah managers to integrate these three factors into their human resource development strategies, creating a competent and productive teaching staff.